Philosophy and Paradigm in Health Studies: A context of Migration and Fertility - Ngmenbelle, David (International Research Journal of MMC, 2025)
Postgraduate research is an important course carried out to solve an existing problem through policy and decision-making process. However, it is significant that research philosophy and paradigm be clearly declared in postgraduate research. Yet, this has been marginalized in health studies among postgraduate students. The paper contributes to scientific literature by guiding postgraduate students, particularly in public health. It highlights the relevance of adopting or choosing the appropriate research methods. This means that as is just section of my thesis, it sounds relevant to contribute existing literature. Though in the main study, cross-sectional design was used and source of data provided with a comprehensive analysis, these are considered in the other articles but for this, it is much particular about methodology or philosophy which is basically is not captured in most postgraduate studies and that what this article focuses on. The paper attempts to guide novice researchers on the choice of appropriate research paradigm. It outlined the concepts of ontology (the nature of reality), epistemology (how knowledge is acquired), and axiology (the role of values in research). It further explains key paradigms including positivism (objective and measurable reality), interpretivism (understanding subjective meanings), critical theory (challenging power structures), postmodernism (embracing multiple realities), and pragmatism (using methods that best address the research problem). In the context of migration and fertility, it has been suggested that these paradigms remain relevant though they pursue varied objectives.